2019
DOI: 10.1177/1177932219884297
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Screening and Analysis of Broad-Spectrum Molecular Targets and Lead Compounds for Diarrhea Therapy

Abstract: Diarrhoeal disease kills about 1.5 million human beings per year across the continents. The enterotoxigenic Escherichia coli (ETEC) pathotype has been noted as a major cause of diarrheal disease in human and livestock. The aim of this study is to identify broad-spectrum molecular targets in bacteria and broad-spectrum lead compounds (functional inhibitors) with high efficacy and no significant adverse implication on human systems, in relevance to diarrhea therapy through computational approaches which include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…Besides, there are pieces of evidence showing that bioinformatics is a very reliable epidemiological tool during disease and antimicrobial resistance surveillance (Bessoff et al, 2013;Gardner and Hall, 2013;Kaiser et al, 2016;Yodmeeklin et al, 2017). Also, with bioinformatics applications, scientists are already discovering new drug targets for the treatment of diarrhoeal diseases (Allan, 2014;Ugboko et al, 2019).…”
Section: Bioinformaticsmentioning
confidence: 99%
“…Besides, there are pieces of evidence showing that bioinformatics is a very reliable epidemiological tool during disease and antimicrobial resistance surveillance (Bessoff et al, 2013;Gardner and Hall, 2013;Kaiser et al, 2016;Yodmeeklin et al, 2017). Also, with bioinformatics applications, scientists are already discovering new drug targets for the treatment of diarrhoeal diseases (Allan, 2014;Ugboko et al, 2019).…”
Section: Bioinformaticsmentioning
confidence: 99%
“…The dynamics of P-gp structure (PDB: 6C0V, chain A) was investigated according to the method of Ugboko et al 25 at pH 7.5. Briefly, from the crystal structure (X-ray structure), PDBFixer implemented in OpenMM v7.3 26 on CPU platform was used to fix the protein.…”
Section: Methodsmentioning
confidence: 99%
“…https://www.drugbank.ca/drugs/DB01087, which is active against gametocytes as well as recalcitrant parasitic forms of malaria, and therefore useful for preventing vivax and ovale relapse [70]. None of these four compounds has any previously documented antibacterial activity (in vivo or in vitro) against Gram negative bacteria, however, Ugboko et al (2019) in an in silico screen and analysis of broad-spectrum molecular targets and lead compounds for potential anti-diarrhoea agents reported MMV687800 as one of the compounds with predicted activity against potential targets for diarrhoea disease among twenty five other compounds [71]. Low et al (2017) in screen to identify TB active compounds against nontuberculous Mycobacterium additionally retrieved MMV687800 as an M. avium-specific main hits among five other MMV compounds [72] and Hennessey et al (2018) also reported MMV687800 among seven MMV compounds as an inhibitor with dual efficacy against Giardia lamblia and Cryptosporidium parvum in a pathogen box screen [73].…”
Section: Primaquine (Mmv000023mentioning
confidence: 99%